OP25 Targeting endoscopic outcomes through combined pharmacokinetic and pharmacodynamic monitoring of infliximab therapy in patients with Crohn's disease. (25th January 2019) - Dreesen, E; Baert, F; Laharie, D; Bossuyt, P; Bouhnik, Y; Buisson, A; Lambrecht, G; Louis, E; Oldenburg, B; Pariente, B; Pierik, M; van der Woude, C J; et al.
Abstract: Background: In TAILORIX, infliximab (IFX) trough concentrations (TC) >23.1 mg/l at Week 2 and >10.0 mg/l at Week 6 predicted endoscopic remission (Crohn's disease (CD) endoscopic index of severity <3) at Week 12. 1 During maintenance therapy, no exposure–response relation was observed, but faecal calprotectin (FC) was lower in patients achieving the endoscopic outcomes compared with patients who did not. 1 Methods: A two-compartment population PK (popPK) model was developed based on data from 1329 samples from 116 patients in TAILORIX (NONMEM 7.4). 2 Results: In line with the previously observed higher IFX TC, 1 also the estimated IFX clearance (CL) during induction therapy was lower in patients achieving endoscopic remission at Week 12 (−0.067 ± 0.020 l/day, p = 0.001), but this was not observed during maintenance therapy ( P > 0.05). During maintenance therapy, an exposure–response relationship was observed only after dose escalation, with a TC >10.8 mg/l after dose escalation predicting the absence of ulcers at Week 54 (Figure 1A). However, this exposure–response relation only appeared after three infusions at the elevated dose (Figure 1B). Furthermore, in patients with elevated FC (>250 mg/kg), a significant drop was observed right upon dose escalation, resulting in FC concentrations that were lower in patients without ulcers compared with patients with ulcers ( p = 0.033) (Figure 1C). Antibodies to IFX (ATI), measured using a drug-tolerant assay, increased IFX CL with 48%, resulting in a reduction of the terminal half-life from 9.4 to 6.4 days (Table 1). Even when dose escalations masked the detection of ATI, the popPK model still estimated an effect of ATI on IFX CL. In addition, IFX exposure reduced when albumin was lower and FC and fat-free mass were higher. Conclusions: We recommend proactive and reactive monitoring of FC during IFX maintenance therapy, but when FC does not normalise upon dose escalation, the IFX TC provides information on the mechanism of failure and can thus guide clinical decision-making (Figure 2). Future prospective trials are needed to evaluate this proposed TDM algorithm. (A) Density plot and ROC curve and (B) boxplots representing the relation between IFX TC after dose escalation and the absence/presence of ulcers at Week 54. (C) The difference in FC upon dose escalation (T1) between patients with/without ulcers at Week 54. References 1. Dreesen E, D'Haens G, Baert F, et al. DOP047 infliximab exposure predicts superior endoscopic outcomes in patients with active Crohn's disease: pharmacokinetic–pharmacodynamic analysis of TAILORIX, ECCO, 2018.https://www.ecco-ibd.eu/publications/congress-abstract-s/abstracts-2018/item/dop047-infliximab-exposure-predicts-superior-endoscopic-outcomes-in-patients-with-active-crohn-x2019-s-disease-pharmacokinetic-x2013-pharmacodynamic-analysis-of-tailorix.html 2. D'Haens G, Vermeire S, Lambrecht G, et al. Increasing infliximab dose based on symptoms, biomarkers, and serum drug concentrations does not increase clinical, endoscopic, and corticosteroid-free remission in patients with active luminal Crohn's disease. Gastroenterology 2018;154:1343–1351.e1.